Effects of m6A methylation of MAT2A mRNA regulated by METTL16 on learning and memory, hippocampal synaptic plasticity and Aβ1–42 in 5 × FAD mice - Chen, Huan; Guo, Fangzhen; Zhao, Yan; Liu, Wei; Chen, Bingyu; Wang, Chang; Huang, Lining; Jiang, Sufang; Ma, Xiaowei; Ren, Huiling; Li, Sha; Cui, Huixian (Frontiers in Aging Neuroscience, 2025)
BackgroundAlzheimer’s disease (AD) is a common neurodegenerative disorder affecting older adults, characterized by progressive cognitive decline and pathological features such as amyloid plaque deposition, neuronal loss, and synaptic reduction. RNA N6-methyladenosine (m6A) methylation is prevalent in the brain and is intricately linked to synaptic plasticity, learning, and memory in AD. However, the precise mechanisms underlying these associations remain elusive.MethodsThis study employed the overexpression of methyltransferase-like protein 16 (METTL16), or overexpression of methionine adenosyltransferase 2A (MAT2A), or a combination of METTL16 overexpression with MAT2A knockdown to explore the influence of METTL16 on the regulation of MAT2A in cognitive function, hippocampal synaptic plasticity, and amyloid-beta (Aβ1–42) metabolism in 5 × FAD mice.ResultsOur findings indicated a reduction in m6A methylation levels and the expression of METTL16 and MAT2A in the hippocampus of 5 × FAD mice. Overexpression of METTL16 led to an increase in overall m6A methylation levels, furthermore, overexpression of either METTL16 or MAT2A enhanced learning and memory in 5 × FAD mice, elevated the expression levels of postsynaptic density 95 (PSD95) and synaptophysin (Syp), increased dendritic spine density, and decreased the accumulation of Aβ1–42 in the hippocampus. In the hippocampus of 5 × FAD mice, METTL16 was found to upregulate both the protein and mRNA levels of MAT2A, as well as enhance MAT2A mRNA m6A methylation levels. Concurrent, overexpression of METTL16 and knockdown of MAT2A in the hippocampus resulted in impaired learning and memory in 5 × FAD mice, alongside a reduction in synaptic protein expression and dendritic spine density, and an increase in Aβ1–42 accumulation.ConclusionThe present study demonstrated that METTL16 enhances learning and memory in 5 × FAD mice by regulating MAT2A mRNA m6A methylation, which leads to increased expression levels of PSD95 and Syp, greater dendritic spine density, and reduced Aβ1–42 accumulation in the hippocampus. These findings reveal a novel approach for investigating the pathophysiological role of METTL16 in AD and offer new insights for developing of potential therapeutic targets for AD.